Effect of Thermal Treatment on the Photocatalytic Activity in Visible Light of TiO2-W Flame Spray Synthesised Nanopowders - Michalow, Katarzyna A.; Heel, Andre; Vital, Andri; Amberg, Martin; Fortunato, Giuseppino; Kowalski, Kazimierz; Graule, Thomas J.; Rekas, Mieczyslaw (Topics in catalysis, 2009)
Effect of W doping as well as a thermal treatment on the structural and photocatalytic properties of TiO 2 produced by flame spray synthesis (FSS) were the subject of investigation. Structural properties were studied by means of X-ray diffraction (XRD), BET adsorption isotherm and transmission electron microscopy (TEM). The surface condition was investigated by X-ray photoelectron spectroscopy (XPS) and differential scanning calorimetry (DSC) and differential thermal and thermogravimetric analysis (DTA-TGA). The photocatalytic properties were studied by optical measurements and photodecomposition of methylene blue under visible irradiation. It was found that the photoactivity in the visible region was enhanced significantly by the W-doping as well as by additional thermal treatment of those nanopowders. The obtained TiO 2 -W nanopowders exhibited higher performance under visible light than P25.